2022
DOI: 10.3390/coatings13010004
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Doped TiO2 Thin Film as an Electron Transfer Layer for Perovskite Solar Cells: A Review

Abstract: The electron transfer layer (ETL) plays a vital role in achieving high-performance perovskite solar cells (PSCs). Titanium dioxide (TiO2) is primarily utilised as the ETL since it is low-cost, chemically stable, and has the simplest thin-film preparation methods. However, TiO2 is not an ideal ETL because it leads to low conductivity, conduction band mismatch, and unfavourable electron mobility. In addition, the exposure of TiO2 to ultraviolet light induces the formation of oxygen vacancies at the surface. To o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…On the other hand, several reports state that the pristine TiO 2 contains numerous trap states (caused by oxygen vacancies), which decrease its carrier mobility and conductivity. , Moreover, the higher defect density on the surface of the TiO 2 lowers the charge carrier separation at the interface of the perovskite and ETL . Varying the calcination temperature of the material is the commonly used approach for suppressing oxygen vacancies. , However, incorporating metal impurities into the lattice of TiO 2 not only passivates these trap states but also enhances the conductivity of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several reports state that the pristine TiO 2 contains numerous trap states (caused by oxygen vacancies), which decrease its carrier mobility and conductivity. , Moreover, the higher defect density on the surface of the TiO 2 lowers the charge carrier separation at the interface of the perovskite and ETL . Varying the calcination temperature of the material is the commonly used approach for suppressing oxygen vacancies. , However, incorporating metal impurities into the lattice of TiO 2 not only passivates these trap states but also enhances the conductivity of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…An electron transport layer must comply with some requirements: (1) well-matched energy alignment to trigger electron transfer while blocking holes; (2) high transparency to allow efficient light harvesting; and (3) excellent electron mobility to minimize charge accumulation [20][21][22][23][24]. TiO 2 offers high performance as an ETL in PSCs due to its alignment of the TiO 2 conduction band with the perovskite layer [25][26][27]; furthermore, the percentage of transparency of TiO 2 is greater than 85% in practically all spectral windows [28].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the geometry of ETL plays an important role in PSCs to maximize device performance. The implementation of TiO 2 nanocolumns as an ETL presents great advantages compared to flat and mesoporous layers when constructing a PSC [ 27 , 33 , 34 , 35 ], as it provides greater stability and efficiency by means of some advantages: (i) an enhanced contact zone between perovskite and ETL, and increased exciton generation; (ii) the 1D morphology offers a directive path for electron transport to the TCO substrate and minimizes resistance to charge transport; and (iii) larger nanorods improve the light scattering and absorption properties of PSCs [ 45 ]. It has been found that the presence of semiconductor metal oxides is not unique.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ETL layer plays a very important role in the efficiency and stability of the PSC [5]. The material commonly used as ETL is titanium dioxide (TiO 2 ) due to its excellent properties, including a simple synthesis process, better hole-blocking properties, high optical transparency, and high thermal stability [6][7][8].…”
Section: Introductionmentioning
confidence: 99%